Project-Based Learning for Teaching Software Engineering: An Experience Report - Vieira, Bernardo J. da S.; Rocha, Lucas D. S. da; Morais, Ceres G. B.; Lopes, Maximiliano A. da S.; R. Neto, Pedro F.; B. Neto, Raimundo N.; Rodrigues, Gabryella R. (Anais do Workshop de Informática na Escola (WIE); 2025: Anais do XXXI Workshop de Informática na Escola, 2025)
Introduction: Software Engineering education requires the development of both technical and interpersonal skills. In this context, Project-Based Learning (PBL) has stood out for increasing student engagement and fostering the practical application of course content. Objective: Accordingly, this study aims to report on the implementation of PBL in the Software Engineering I course of a Computer Science program at a public university. Methodology: To this end, an exploratory action research approach was adopted, with data collected through participant observation, questionnaires, and interviews. Students developed software projects for real clients, going through the stages of requirements elicitation, modeling, design, and prototyping. Results: The data revealed increased student engagement, development of technical and socio-emotional skills, and a positive perception of the methodology used. Thus, this experience highlights the potential of PBL to integrate theory and practice in Software Engineering education.